PERFORMANCE EVALUATION ON DRILLING OF AUSTENITIC STAINLESS STEEL 316L USING HSS TOOL (Jurnal Mekanikal, 2018)
This paper presents the effect of drilling parameters on tool wear, tool life, surface roughness, dimensional accuracy and roundness when drilling austenitic stainless steel 316L using HSS tool. Experimental trials were conducted at different cutting speeds of 10, 16 and 22 m/min with constant feed rates of 0.05 and 0.075 mm/rev and under dry and coolant conditions. Results showed that the number of drilled holes was significantly influenced by the cutting speed whereby increasing cutting speed decreases the number of holes. Surface roughness measurement showed that better surface finish was obtained at lower cutting speed and feed rate. Results also showed that the dimensional accuracy at lower feed rate is better than at higher feed rate. From the roundness aspect, it was found that the new tool contribute to the good roundness compared to the worn tool.
Keywords: Drilling; Tool wear; Surface roughness; Dimensional accuracy; Roundness